2010
DOI: 10.1007/s11999-009-1224-9
|View full text |Cite
|
Sign up to set email alerts
|

Results after Late Polymicrobial, Gram-negative, and Methicillin-resistant Infections in Knee Arthroplasty

Abstract: Background Previous studies of knee arthroplasty infections caused by high-virulence organisms suggest poor outcomes. Polymicrobial and Gram-negative infections are less studied. Questions/purposes This study compared the results of treatment of knee arthroplasty infections by single versus polymicrobial isolates, Gram-positive versus Gram-negative, and methicillin-resistant versus -sensitive Staphylococci. Methods We prospectively followed 47 patients with late knee arthroplasty infections. The mean age was 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…10,15 However, the infection control rate improved to 100% after repeated debridement and repeated 2-stage revision. Cordero-Ampuero et al 14 reported that 34 (81%) of 42 late chronic infections treated with debridement or 2-stage exchange arthroplasty maintained functioning total knee prostheses at the last evaluation, similar to the findings of the current study (76%). In addition, the current study investigated the number of operations needed for eradication of infection.…”
Section: Results Of Acute Early Infection Based On Resistant Organismsupporting
confidence: 89%
See 1 more Smart Citation
“…10,15 However, the infection control rate improved to 100% after repeated debridement and repeated 2-stage revision. Cordero-Ampuero et al 14 reported that 34 (81%) of 42 late chronic infections treated with debridement or 2-stage exchange arthroplasty maintained functioning total knee prostheses at the last evaluation, similar to the findings of the current study (76%). In addition, the current study investigated the number of operations needed for eradication of infection.…”
Section: Results Of Acute Early Infection Based On Resistant Organismsupporting
confidence: 89%
“…12,13 However, they did not compare infections with and without resistant organisms or classify infections as early vs late. Cordero-Ampuero et al 14 reported 47 late TKA infections and found no difference in the eradication of MRSA/ MRSE and non-MRSA/MRSE infections. However, these authors did not investigate differences in eradication at initial treatment, functional prosthetic knees, and the number of operations between MRSA/ MRSE and non-MRSA/MRSE infections.…”
mentioning
confidence: 97%
“…Additionally, two-stage reimplantation is reported to be even more successful when used in low-grade TKA infections [2, 4, 9, 39, 4648]. Volin et al [48] reported a 94.6 % success rate in methicillin-sensitive S. aureus infections.…”
Section: Resultsmentioning
confidence: 99%
“…Other retrospective studies with eight to 21 patients had higher rates of infection control between 87% and 93% [6,23,40,52] (Table 1). Patients with infections caused by methicillinresistant Staphylococcus aureus (MRSA) or methicillinresistant Staphylococcus epidermidis (MRSE) were not included in these studies; infections with these pathogens generally have lower rates of infection control than periprosthetic infections with other pathogens [10,31,38,39]. None of these studies report function (as reflected by knee scores) or analyses of potential factors that influence the rate of infection control after one-stage revisions.…”
Section: Introductionmentioning
confidence: 99%